Evaluating the hourly emissions intensity of the US electricity system. (1st April 2023) - Miller, Gregory J; Pease, Gailin; Shi, Wenbo; Jenn, Alan
Abstract: High-quality data for the greenhouse gas and air pollution emissions associated with electricity generation and consumption are increasingly important to enable effective and targeted action to decarbonize the electric grid and to inform research in a range of academic disciplines including environmental economics, lifecycle assessment, and environmental health. To inform the broadest range of use cases, such data should ideally have a high temporal and spatial resolution, be available in as close to real-time as possible, represent the complete power sector, use the highest-quality measured data, have complete historical coverage, and represent both generated and consumed emissions. To date, no published datasets have achieved all of these characteristics. This work is the first to publish a comprehensive, plant-level dataset of hourly-resolution generation, fuel consumption, and direct CO2, NOx, and SO2 emissions for the entire U.S. power sector. This data is published as part of the public and open-source Open Grid Emissions Initiative, which also includes hourly, consumption-based emissions intensities for every grid balancing area in the country. Using insights generated by this new dataset, this paper also interrogates how several of the assumptions implicit in the use of existing power sector emissions datasets may under-count or misrepresent the climate and health impacts of air emissions from the U.S. power sector. We envision the Initiative becoming a central repository of, and hub of activity for addressing open research questions related to power sector emissions data, and the go-to source for high-quality, high-resolution data for future research on grid emissions.